Phylogeny of All Recognized Species of Ammonia Oxidizers Based on Comparative 16S rRNA and amoA Sequence Analysis: Implications for Molecular Diversity Surveys - Purkhold, Ulrike (American Society for Microbiology, 2000)
The current perception of evolutionary relationships and the natural diversity of ammonia-oxidizing bacteria (AOB) is mainly based on comparative sequence analyses of their genes encoding the 16S rRNA and the active site polypeptide of the ammonia monooxygenase (AmoA). However, only partial 16S rRNA sequences are available for many AOB species and most AOB have not yet been analyzed on the amoA level. In this study, the 16S rDNA sequence data of 10 Nitrosomonas species and Nitrosococcus mobilis were completed. Furthermore, previously unavailable 16S rRNA sequences were determined for three Nitrosomonas sp. isolates and for the gamma-subclass proteobacterium Nitrosococcus halophilus. These data were used to revaluate the specificities of published oligonucleotide primers and probes for AOB. In addition, partial amoA sequences of 17 AOB, including the above-mentioned 15 AOB, were obtained. Comparative phylogenetic analyses suggested similar but not identical evolutionary relationships of AOB by using 16S rRNA and AmoA as marker molecules, respectively. The presented 16S rRNA and amoA and AmoA sequence data from all recognized AOB species significantly extend the currently used molecular classification schemes for AOB and now provide a more robust phylogenetic framework for molecular diversity inventories of AOB. For 16S rRNA-independent evaluation of AOB species-level diversity in environmental samples, amoA and AmoA sequence similarity threshold values were determined which can be used to tentatively identify novel species based on cloned amoA sequences. Subsequently, 122 amoA sequences were obtained from 11 nitrifying wastewater treatment plants. Phylogenetic analyses of the molecular isolates showed that in all but two plants only nitrosomonads could be detected. Although several of the obtained amoA sequences were only relatively distantly related to known AOB, none of these sequences unequivocally suggested the existence of previously unrecognized species in the wastewater treatment environments examined.